Towards a reframing of student support: a case study approach - Roberts, Pamela; Dunworth, K.; Boldy, Duncan (Springer, 2018)
© 2017, Springer Science+Business Media Dordrecht. This paper reports on a study that investigated the range of institutional support needs of international students at one Australian university with a view to increasing understanding of their needs and the ways in which support was provided. The study involved a number of data collection methods including focus groups, key informant interviews and a larger scale survey, undertaken in an inductive and sequential process. The results indicated that the levels of awareness about services differed, that lack of knowledge of how to access a service and finding information about it were key reasons for non-use, and that the helpfulness of staff impacted on the perception of services as useful. The paper concludes by recommending a reconsideration of current practices to move towards a model of student support service provision in which the student is at the centre.